(3QSGdI GdWQbs - (3GdocrHQi GdpNjhbj GdNhGQRej, CHh GdLfGH, fLe GdOjf, CMeO Hf YeQ Hf eMqeO, J(B618(3g`s ((3MGLj Hf EHQGgje Hf Ydj GdJQGHjs)
(3ChdgG (B:s
(3GdMeO ddg ChdG hBNQGbGdfLe GdOjf CHh GdNHGH CMeO Hf YeQ Hf eMeO Hf YHO Gddg Gdefhaj GdUhajChdgG WQjb CQHGH GdeYGedGJ HcKQI GdUhe hGdUdGI hJdGhI GdbQBfs
(3BNQgG (B:s
(3TLQI GdEfSGfjI djS HNGQL efgG dGHRgQjI GdeDefjI hdG HKeGf GdhdGjI hGdfHhI Jage Ef TGA Gddgs
(3ebGHdI Ydi fSNI HNW LGeYgG aj GdbOS GdTQjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 185s
(3eYLe GdeDdajf(B: 1 / 218s
(3cTa GdXfhf(B: 1 / 876s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs